2020
DOI: 10.1016/j.ijscr.2020.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric allergic fungal rhinosinusitis with extensive intracranial extension – Case report and literature review

Abstract: Highlights Allergic fungal sinusitis (AFRS) has become increasingly common. It’s defined as a noninvasive, benign inflammatory fungal disease of the sinuses which develops in young adults and adolescents. AFRS can present clinically in different ways. Its presentation can range from simple nasal obstruction to signs and symptoms of intra-orbital and/or intracranial complications. In pediatric cases being very aggressive, Careful clinical evaluation, detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Patients with nasal polyps had a history of asthma (20%); Anatomical abnormalities such as DNS, turbinate hypertrophy, but no significant correlation with AFS Goldstein also reported a history of atopy in one third of patients and asthma in one third of AFS. As reported by Yousuf M et al, Nasal polyps were strongly associated with AFS [17][18] . Radiological assessments showed multinuclear occupation with areas of attenuation surrounded by the area of hypodensity in most of our cases.…”
Section: Discussionsupporting
confidence: 59%
“…Patients with nasal polyps had a history of asthma (20%); Anatomical abnormalities such as DNS, turbinate hypertrophy, but no significant correlation with AFS Goldstein also reported a history of atopy in one third of patients and asthma in one third of AFS. As reported by Yousuf M et al, Nasal polyps were strongly associated with AFS [17][18] . Radiological assessments showed multinuclear occupation with areas of attenuation surrounded by the area of hypodensity in most of our cases.…”
Section: Discussionsupporting
confidence: 59%
“…Allergic fungal rhinosinusitis (AFRS) is a noninvasive fungal sinusitis that is characterized by alterations in the innate immunity, type 2 inflammation with alteration in sino nasal adaptive immune response, and direct involvement of fungal elements in the pathogenesis [2]. Although AFRS is more commonly seen among adults, it can also occur in children, but there is a scarcity of literature on its clinical course in this age group [3]. Studies suggest that the clinical presentation of AFRS in children is subtle, with a slow onset of symptoms, and often involves facial dysmorphism [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed no histological evidence of fungal invasion of the mucosa. Pressure atrophy due to the expansion of mucoceles and polyps is the causative factor in AFRS-related bone erosion (Alenzi et al, 2020). Allergic mucin produces inflammatory mediators, which contribute to bone erosion.…”
Section: Discussionmentioning
confidence: 99%